Gothic Tourism - McEvoy, Emma.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
From Strawberry Hill to The Dungeons, Alnwick Castle to Barnageddon, Gothic tourism is a fascinating, and sometimes controversial, area. This lively study considers Gothic tourism's aesthetics and origins, as well as its relationship with literature, film, folklore, heritage management, arts programming and the 'edutainment' business.
Keywords: Communication; Arts; Children's literature; Media and Communication